2013
DOI: 10.1264/jsme2.me13048
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Archaeal Diversity in an Iron-Rich Coastal Hydrothermal Field in Yamagawa, Kagoshima, Japan

Abstract: Physicochemical characteristics and archaeal and bacterial community structures in an iron-rich coastal hydrothermal field, where the temperature of the most active hot spot reaches above 100°C, were investigated to obtain fundamental information on microbes inhabiting a coastal hydrothermal field. The environmental settings of the coastal hydrothermal field were similar in some degree to those of deep-sea hydrothermal environments because of its emission of H2, CO2, and sulfide from the bottom of the hot spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…However, this microorganism appears to have increased the EET ability by organizing filaments into bundled structures ( Figures 1a,b ), a possible strategy for achieving a c -cyt density allowing electron percolation along entire filaments ( Broadbent and Hammersley, 1957 ). Additionally, the clustering of microbially reduced and conductive iron oxide minerals on the cell surface of strain 110S also facilitated electron transfer in the natural environment through self-constructed bacterial networks ( Nakamura et al, 2009b , 2013 ), which may allow strain 110S to inhabit an iron-rich sediment with the ability to reduce extracellular iron minerals ( Kawaichi et al, 2013b ). Consistent with this speculation, ferrihydrite greatly increased both the maximum current generation and dulation of current generation by strain 110S ( Figure 3 and Supplementary Figure S3 ), which in turn resulted in the large increase in the number of viable cells in the multicellular filament.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this microorganism appears to have increased the EET ability by organizing filaments into bundled structures ( Figures 1a,b ), a possible strategy for achieving a c -cyt density allowing electron percolation along entire filaments ( Broadbent and Hammersley, 1957 ). Additionally, the clustering of microbially reduced and conductive iron oxide minerals on the cell surface of strain 110S also facilitated electron transfer in the natural environment through self-constructed bacterial networks ( Nakamura et al, 2009b , 2013 ), which may allow strain 110S to inhabit an iron-rich sediment with the ability to reduce extracellular iron minerals ( Kawaichi et al, 2013b ). Consistent with this speculation, ferrihydrite greatly increased both the maximum current generation and dulation of current generation by strain 110S ( Figure 3 and Supplementary Figure S3 ), which in turn resulted in the large increase in the number of viable cells in the multicellular filament.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, cells in the oxidative zone uptake electrons from the extracellular insoluble electron donor coupled with the half reaction of nitrate reduction via the denitrification pathway ( napAB, nirK, norBC , and nosZ ) (cathodic EET). Thus, the ability of anodic and cathodic EET facilitate the interface of cellular metabolism with the segregated biogeochemical reactions in the sediments of a coastal hydrothermal field ( Kawaichi et al, 2013b ). Although the present study demonstrated the ability of the multicellular filamentous bacteria to conduct bidirectional EET for dissipating spatially segregated redox potentials in a form of electrical current, no direct evidence for the long-range electron transport along the filament was provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial and archaeal diversity was determined within the iron-rich coastal hydrothermal field of Yamagana beach (Kawaichi et al, 2013b). The results of clone analyses based on 16S rRNA genes revealed chemolithoautotrophic thermophiles, primarily within the bacterial order Aquificales and chemoheterotrophic thermophiles from the order Thermales and the family Desulfococcaceae.…”
Section: Kagoshima Bay (Japan)mentioning
confidence: 99%
“…Yet, a limited number of them have been isolated to date. Ardenticatena maritima strain 110S T is isolated from an iron-rich coastal hydrothermal field and described as the first, and to date, sole isolate in the phylum to be capable of iron and nitrate reduction ( 1 , 2 ). Although the 16S rRNA gene sequence of strain 110S shared low (<84%) nucleotide identity with that of other isolates, highly similar sequences were found in uncultured microbes from high-temperature metal-rich environments, such as an arsenic- and iron-rich shallow sea hydrothermal vent in Papua New Guinea ( 3 ).…”
Section: Genome Announcementmentioning
confidence: 99%